-2(4z-3)+9(z-6)=-32-8

Simple and best practice solution for -2(4z-3)+9(z-6)=-32-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(4z-3)+9(z-6)=-32-8 equation:


Simplifying
-2(4z + -3) + 9(z + -6) = -32 + -8

Reorder the terms:
-2(-3 + 4z) + 9(z + -6) = -32 + -8
(-3 * -2 + 4z * -2) + 9(z + -6) = -32 + -8
(6 + -8z) + 9(z + -6) = -32 + -8

Reorder the terms:
6 + -8z + 9(-6 + z) = -32 + -8
6 + -8z + (-6 * 9 + z * 9) = -32 + -8
6 + -8z + (-54 + 9z) = -32 + -8

Reorder the terms:
6 + -54 + -8z + 9z = -32 + -8

Combine like terms: 6 + -54 = -48
-48 + -8z + 9z = -32 + -8

Combine like terms: -8z + 9z = 1z
-48 + 1z = -32 + -8

Combine like terms: -32 + -8 = -40
-48 + 1z = -40

Solving
-48 + 1z = -40

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '48' to each side of the equation.
-48 + 48 + 1z = -40 + 48

Combine like terms: -48 + 48 = 0
0 + 1z = -40 + 48
1z = -40 + 48

Combine like terms: -40 + 48 = 8
1z = 8

Divide each side by '1'.
z = 8

Simplifying
z = 8

See similar equations:

| 6x+7=(m) | | -20x-(-15x)=-165 | | 11-3(2x+4y)= | | 3x+2=10x-26 | | -8+14=-2(4v-7) | | 5.3+z=-9 | | 25.61+4.1= | | 3(w-3)=w+4-5(-2w-1) | | -2(3Z-5)+7(z-7)=-13-6 | | 9x^4-66x^2+121=0 | | 25r-25r+25r=5-2.5r | | n+6=96 | | -(y+15)+2y-12=-27 | | x^4-x^2=47x^2+49 | | -3(3u-1)+5u=9+4(2u-4) | | (7r^3-6r-6)(2r-4)= | | 62(x+20)=90 | | -(y+15)+2y-12=-42 | | t^3-10t+21=0 | | 9(s+6)-8s=45 | | 12x+11=13x+9 | | 4(8)+3y=35 | | 16t^2-96t-12=152 | | -1.8-3=7w-5.5-6w | | 12-40= | | 16-(2m+8)=4+3m-11 | | 4(w-5)-6=-4(-4w+9)-6w | | -10-6p+7p=-9 | | -21x-63=-126 | | 3x/4x-5/6=2x/3x | | 8s-4-7s=2-1 | | -0.53k=3.498 |

Equations solver categories